The new poverty agenda in Uganda - Anne Mette Kjær; Fred Muhumuza (Danish Institute for International Studies (DIIS), 2009)
This paper explores the poverty agenda in Uganda, its drivers and its effects. We show that transforming the economy by increasing productivity was initially considered more important than to reduce poverty through redistributive policies. However, as a consequence of the 1996 elections a consensus on poverty eradication through health and education emerged. The Poverty Eradication Action Plan (PEAP) had a shopping list nature and it is therefore difficult to establish whether it was implemented. Growth and poverty reduction during the PEAP period was mainly due to a continuation of macro-economic policies that were introduced prior to the PEAP. Around the multi-party elections in 2006, policy priorities changed towards more focus on agricultural production, agro-business and infrastructure. The government now has a two-edged focus: poverty reduction through economic transformation and poverty reduction through social services. However, there is also a political agenda about remaining in power which threatens to undermine the results achieved so far.
Keywords: 330; Armutspolitik; Wachstumspolitik; Uganda